Trans Bekasi Patriot Bus Users Perception Of Integrated Mass Transportation: An Empirical Phenomenological Study: Persepsi Pengguna Bus Trans Bekasi Patriot Terhadap Transportasi Massal Terintegrasi: Studi Fenomenologi Empiris - Puja Yehuda Ginting; Hanny Purnamasari; Mochamad Faizal Rizki (Universitas Indo Global Mandiri, 2026)
Purpose : To analyze how users construct meanings of their experiences and to identify key issues in service delivery as a basis for improving transport policy and practice Design/methodology/approach : A qualitative empirical phenomenological approach using in-depth interviews, non-participant observation, and document analysis; data were analyzed through phenomenological reduction, thematic clustering, and interpretation of experiential essence Findings : The service is perceived as affordable, comfortable, and safe; however, quality is affected by schedule inconsistency, limited routes, and inadequate bus stop facilities, resulting in a gap between policy design and operational reality Practical Implication : User experience serves as a reflective evaluation instrument, encouraging a human-centered policy evaluation approach to improve service quality, responsiveness, and public trust. Originality/value : Offers a phenomenological perspective on peri-urban mass transit by emphasizing user experience as a foundation for transport policy development Paper type : Research paper